UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DI KELAS V SD NEGERI 050600 KUALA LANGKAT TAHUN PEMBELAJARAN 2017/2018 - NOVA FITRI JAYANTI, NOVA FITRI (Jurnal Ilmiah Aquinas, 2018)
This study aims to (1) improve mathematics learning outcomes by using jigsaw type cooperative learning model in grade 5 students of SD Negeri 050600 Kuala Langkat Learning Year 2017/2018. (2) Describe the constraints encountered by using jigsaw type cooperative learning model to improve mathematics learning outcomes. The results of this study indicate an increase in student learning outcomes on subjects mathematics material KPK and FPB class V Elementary School 050600 Kuala Langkat. This is evident from the results of research conducted on the pretest of students who got the complete value of 5 people or 21.73% while the students who did not complete as many as 18 people or 78.27%. Then continued research research on the first cycle of students who got the complete value of 14 people or 60.86% while the unfinished students as many as 9 people or 39.14%, then there is an increase in increase in cycle I compared to pretest. But this does not meet the specified category of mastery. Then proceeded on the second cycle of students who get a total score of 20 people or 86.95% while students who are not complete as many as 3 people or 13.05%, then an increase in cycle II compared to cycle I and has fulfilled the specified mastery . Furthermore, teacher activity on observation cycle I obtained an average of 60% and in cycle II increased to 78%. While the student activity on the learning process obtained an average of 58% and in the second cycle has increased to 84%. Thus obtained the conclusion that by using cooperative learning model type jigsaw on subjects mathematics material KPK and FPB in class V SDÂ  050600 Kuala Langkat can improve student learning outcomes. Therefore it is suggested for subsequent learning to use cooperative learning model of jigsaw type so that student learning result can increase